A prospective study of paediatric preoperative fasting times at Red Cross War Memorial Children's Hospital - Kouvarellis, Alison (Department of Anaesthesia and Perioperative Medicine, 2022)
Background. Fasting for liquids and solids is recommended prior to procedures requiring anaesthesia, to reduce the risk of pulmonary aspiration. Children often experience excessive fasting, which is associated with negative physiological and behavioural consequences, and patient discomfort. The duration of preoperative fasting in children in South Africa is unknown. Objectives. The aim of this study was to determine the compliance with fasting guidelines and fasting times of children prior to elective procedures performed under anaesthesia at a paediatric hospital in Cape Town, South Africa. The primary focus was fasting for clear liquid. The study also intended to identify the most common reasons for prolonged clear liquid fasting. Methods. Over a seven-week period, we prospectively captured fasting times of consecutive patients undergoing elective surgical, medical and radiological procedures at Red Cross War Memorial Children's Hospital (RCWMCH). Measurement outcomes were defined as the period from the last clear liquid, milk or solid feed to the start of anaesthesia. For analysis of compliance with preoperative fasting guidelines, institutional preoperative fasting target limits were established based on the standard 6-4-2 hour guideline. Results. The study included 721 elective paediatric cases. The mean (SD) fasting time for clear liquids (n=585) was 8.0 (4.8) hours, with an adherence rate of 25.5% (95% confidence interval (CI) 22-29%) to the institutional target of 2 to 4 hours. The mean (SD) fasting times for breast milk (n=92), formula milk (n=116) and solid feeds (n=560) were 7.1 (2.8), 8.8 (2.8) and 13.9 (3.6) hours respectively. The factors associated with clear liquid fasting >4 hours were: inadequate fasting instructions, poor adherence to fasting orders, procedural delays and fasting to promote theatre flexibility. Conclusion. This study demonstrates that children in a South Africa hospital experience excessive fasting times prior to elective procedures. To reduce fasting durations and improve the quality of perioperative care, quality improvement (QI) interventions are required to create an adaptable fasting system which allows individualised fasting. Improving preoperative fasting times in children is the responsibility of all health care professionals in the multi-disciplinary management team.